Long term effect of browse supplementation on live weight gain and scrotal size in male sheep and goats - Kaitho, R.J.; Tegegne, Azage; Umunna, N.N.; Nsahlai, I.V.; Tamminga, S. (British Society of Animal Science, 1997)
This study was conducted to determine the long term effect of supplementation of L. pallida and S. sesban on growth and reproductive performance of male Ethiopian highland sheep and goats fed teff straw (Eragrostis tef) basal diet. The results show that there was no significant effect of the different types of supplements on teff straw intake. However, total intake of dry matter and digestibile organic matter, were significantly affected by the level and the type of supplement.